The association of health-related factors with quality of life among the elderly population in the Jaffna district of Sri Lanka - Sathees Santhalingam; Sivayogan Sivagurunathan; Shamini Prathapan; Sivapalan Kanagasabai; Luxmi Kamalarupan (BMC, 2021)
Abstract Background The proportion of elderly individuals is increasing globally. They should be well cared for to enable them to enjoy their full lifespans. Good health is a vital component of one's overall quality of life. Our study aimed to assess the association of health-related factors with quality of life among elderly individuals in the Jaffna District of Sri Lanka. Methods We conducted a community-based, cross-sectional study among 813 elderly individuals in the Jaffna district of Sri Lanka. Sociodemographic factors and the patterns of health conditions were recorded through an interviewer-administered questionnaire. Quality of life was measured through the World Health Organisation Quality of Life-Bref (WHOQOL-Bref) questionnaire. Results There were slightly more male respondents (53.5%) than females in the study. The median age of the participants was 70 (11) years. Approximately one-third of them had at least one chronic health condition. Musculoskeletal complaints were found to be the most common health condition, followed by diabetes, hypertension, vision problems, and asthma. Among the respondents, 20.1% were attending regular follow-up visits in a clinic, and 24% of them were meeting a doctor at least monthly. Among them, 6.8% had at least one limitation in their activities of daily living. However, the majority (58.6%) reported that they were satisfied with their health status. The following factors were found to be significantly associated with worse quality of life: the presence of health conditions, the presence of musculoskeletal conditions, hearing impairment, vision impairment, bronchial asthma, limitations in activities of daily living, and the use of addictive substances. Satisfaction with health, regular follow-up visits in a clinic, meeting a doctor at least monthly, and having diabetes were significantly associated with better quality of life. Conclusion Minimising the limitations of daily living, abstaining from using addictive substances, preventing diseases, and improving access to health services may enhance the quality of life of elderly individuals. Furthermore, these factors should be considered by policy makers seeking to improve the quality of life of elderly individuals.